2014
DOI: 10.4314/jab.v78i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvesting stages on yield and nutritional quality of African eggplant (<i>Solanum aethiopicum</i> L.) fruits

Abstract: Msogoya et al. J. Appl. Biosci. 2014. Effect of harvesting stages on yield and nutritional quality of African eggplant (Solanum aethiopicum) fruits. ABSTRACT Objective: Farmers often harvest African eggplant (Solanum Aethiopicum L.) fruits at different stages of fruit maturity. The influence of these harvesting practices on fruit productivity and nutritional quality is not known. This study was conducted to determine the effect of harvesting stages on yield and nutritional quality of African eggplant varieties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…Studies have shown that most phenolic compounds are concentrated in the skin surface of fruits (Dadalı, Kılıç Apar, & Özbek, 2007 as reported by Mwende et al (2018). On the other hand, the betacarotene content reported in this study (Table 2) is higher compared to previous reports by Chepngeno, Owino, Kinyuru, and Nenguwo (2016) and Msogoya, Majubwa, and Maerere (2014) on African eggplants. This could suggest a wide variability in the beta-carotene content among African eggplant accessions (Plazas et al, 2014).…”
Section: Discussioncontrasting
confidence: 66%
“…Studies have shown that most phenolic compounds are concentrated in the skin surface of fruits (Dadalı, Kılıç Apar, & Özbek, 2007 as reported by Mwende et al (2018). On the other hand, the betacarotene content reported in this study (Table 2) is higher compared to previous reports by Chepngeno, Owino, Kinyuru, and Nenguwo (2016) and Msogoya, Majubwa, and Maerere (2014) on African eggplants. This could suggest a wide variability in the beta-carotene content among African eggplant accessions (Plazas et al, 2014).…”
Section: Discussioncontrasting
confidence: 66%
“…Carotenoid content built up on CaCl2-treated banana (21.83±0.13 µg/100 g) higher than that on the control (19.07±0.12 µg/100 g) (Table 5). Extended storage induced to a higher loss of carotenoid content, followed by the evolution of ripening (60). The total soluble solid content increased during storage with a lower accumulation on the CaCl2-treated banana (16.40±0.13 o Brix) compared to the control (19.23±0.12 o Brix) (Table 6).…”
Section: Effect Of Cacl2 Post Harvest Treatment On Ascorbic Acid Carotenoid Total Soluble Solid Of Banana Fruit During Storagementioning
confidence: 97%
“…Fruits of the eggplant were harvested at peak maturity state, before the complete seed development, as recommended by Ashtiani et al (2016). This is the stage when eggplants are consume fresh, as the seed are still soft and sequent, while the nutritional qualities of the fruits are at their peak (Msogoya et al, 2014). As this stage, the fruits usually have purple color and glossy skin (Figure 1).…”
Section: Plant Materials Selection and Preparationmentioning
confidence: 99%